Autologous cord blood transplantation for metastatic neuroblastoma. (23rd December 2015) - Ning, Botao; Cheuk, Daniel Ka‐Leung; Chiang, Alan Kwok‐Shing; Lee, Pamela Pui‐Wah; Ha, Shau‐Yin; Chan, Godfrey Chi‐fung
Abstract: Auto‐SCT is a common approach for metastatic neuroblastoma with the intention to rescue hematopoiesis after megadose chemotherapy. PBSC or BM is the usual stem cell source for auto‐SCT. Auto‐CBT for neuroblastoma has very rarely been performed. Currently, case reports are available for two patients only. We performed 13 auto‐SCTs for high‐risk neuroblastoma from 2007 to 2013, including four cases of metastatic neuroblastoma aged 11–64 months treated with auto‐CBT. All four patients had partial or CR to upfront treatments before auto‐CBT. Nucleated cell dose and CD34+ cell dose infused were 2.8–8.7 × 10 7 /kg and 0.36–3.9 × 10 5 /kg, respectively. Post‐thawed viability was 57–76%. Neutrophil engraftment (>0.5 × 10 9 /L) occurred at 15–33 days, while platelet engraftment occurred at 31–43 days (>20 × 10 9 /L) and 33–65 days (>50 × 10 9 /L) post‐transplant, respectively. There was no severe acute or chronic complication. Three patients survived for 1.9–7.7 yr without evidence of recurrence. One patient relapsed at 16 months post‐transplant and died of progressive disease. Cord blood may be a feasible alternative stem cell source for auto‐SCT in patients with stage 4 neuroblastoma, and outcomes may be improved compared to autologous PBSC or BM transplants.